Social Support and Self-Esteem as Predictors of Psychological Well-Being of Generation Z Students - Reo, Gustanto; Soetjiningsih, Christiana Hari; Wijono, Sutarto (Bulletin of Counseling and Psychotherapy, 2024)
There are some generation Z students at college X in Kupang who have low psychological well-being, thus a study was conducted that aims to determine social support and self esteem simultaneously as predictors of psychological well-being of generation Z students at college X Kupang. This study uses quantitative methods and data collection using Ryff's Psychological Well-Being Scale, Multidimensional Scale of Perceived Social Support, Rosenberg Self Esteem Scale distributed via google form to respondents who have met the predetermined criteria. The number of respondents involved was 150 respondents consisting of 40 men and 110 women. The results showed that the Fcount (simultaneous) value was 227,207 with a significance value of 0.000 (p <0.05) this result proves that there is a simultaneous influence of social support and self esteem on the psychological well-being of generation Z students at college X in Kupang with a coefficient of determination of 0.756 meaning that the contribution of the influence of social support and self esteem on psychological well-being is 75.6% the rest is influenced by other variables not examined in this study.